Prolonged storage reduces viability of Peptacetobacter (Clostridium) hiranonis and core intestinal bacteria in fecal microbiota transplantation preparations for dogs - Correa Lopes, Bruna; Turck, Jonathan; Tolbert, M. Katherine; Giaretta, Paula R.; Suchodolski, Jan S.; Pilla, Rachel (Frontiers in Microbiology, 2025)
IntroductionFecal microbiota transplantation (FMT) has been described useful as an adjunct treatment for chronic enteropathy in dogs. Different protocols can be used to prepare and store FMT preparations, however, the effect of these methods on microbial viability is unknown. We aimed (1) to assess the viability of several core intestinal bacterial species by qPCR and (2) to assess Peptacetobacter (Clostridium) hiranonis viability through culture to further characterize bacterial viability in different protocols for FMT preparations.MethodsBacterial abundances were assessed in feces from six healthy dogs by qPCR after propidium monoazide (PMA-qPCR) treatment for selective quantitation of viable bacteria. Conservation methods tested included lyophilization (stored at 4°C and at −20°C) and freezing with glycerol-saline solution (12.5%) and without any cryoprotectant (stored at −20°C). Additionally, the abundance of P. hiranonis was quantified using bacterial culture.ResultsUsing PMA-qPCR, the viability of Faecalibacterium, Escherichia coli, Streptococcus, Blautia, Fusobacterium, and P. hiranonis was reduced in lyophilized fecal samples kept at 4°C and −20°C up to 6 months (p < 0.05). In frozen feces without cryoprotectant, only Streptococcus and E. coli were not significantly reduced for up to 3 months (p > 0.05). Lastly, no differences were observed in the viability of those species in glycerol-preserved samples up to 6 months (p > 0.05). When using culture to evaluate the viability of P. hiranonis, we observed that P. hiranonis abundance was lower in lyophilized samples kept at 4°C than −20°C; and P. hiranonis abundance was higher in glycerol-preserved samples for up to 6 months than in samples preserved without glycerol for up to 3 months. Moreover, the highest abundance of P. hiranonis was observed in glycerol-preserved feces. After 3 months, P. hiranonis was undetectable by culture in 83% (5/6) of the frozen samples without glycerol.DiscussionWhile the lyophilization procedure initially reduced P. hiranonis abundance, P. hiranonis viability was stable thereafter for up to 6 months at −20°C. The higher bacterial viability detected in fecal samples preserved with glycerol confirms the use of this cryoprotectant as a reliable method to keep bacteria alive in the presence of fecal matrix for FMT purposes.